Tracking ‘learning behaviours’ in the incidental acquisition of two dimensional adjectives by Japanese beginner learners of L2 English - Shintani, N.; Ellis, Rod (Arnold, 2014)
The purpose of this article is to examine both the process and product of vocabulary learning in a task-based instructional context. The article reports a study that investigated the acquisition of two dimensional adjectives (‘big’ and ‘small’) by six-year-old Japanese children who were complete beginners. It tracked the ‘learning behaviours’ that occurred in the classroom interactions involving the use of these adjectives in nine task-based lessons to show how these behaviours developed over time. It also collected test data to establish whether the learners had developed the receptive and productive knowledge required for the independent use of two adjectives. In this way, the study shows how second language (L2) learning evolves through interaction by exploring the relationships between the learners’ different learning behaviours and the differences in their test performance. The main finding was that differences in the success of the individual learners in acquiring productive control over the dimensional adjectives – as shown in the tests – was directly traceable to their learning behaviours in the task-based interactions.